Editorial on Special Issue "Precision Delivery of Drugs and Imaging Agents with Peptides" - Kaido Kurrikoff; Tambet Teesalu (MDPI AG, 2022)
Homing peptides and cell-penetrating peptides allow for systemic targeting of diseased tissues and/or efficient intracellular delivery of payloads [...]